(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the impact of information attacks on the minds of young people in the modern information space and the role of family psychology in the formation of moral and spiritual immunity against them. It also highlights the psychological impact of gender stereotypes on the process of raising children and the formation of social consciousness. The scientific study substantiates the importance of the psychological climate in the family, communication culture and upbringing based on values ​​​​in ensuring information security.